Getting started with Linux on Z Encryption for data at-rest - White, Bill (Telecommunications engineer) (IBM redbooks., 2019)
This IBM® Redbooks® publication provides a general explanation of data protection through encryption and IBM Z® pervasive encryption with a focus on Linux on IBM Z encryption for data at-rest. It also describes how the various hardware and software components interact in a Linux on Z encryption environment for . In addition, this book concentrates on the planning and preparing of the environment. It offers implementation, configuration, and operational examples that can be used in Linux on Z volume encryption environments. This publication is intended for IT architects, system administrators, and security administrators who plan for, deploy, and manage security on the Z platform. The reader is expected to have a basic understanding of IBM Z security concepts.